Coordination polymer nanowire diaphragm material, preparation method and application in field of sodium ion battery
By using coordination polymer nanowire separator materials prepared by cheap metal compounds and organic ligands, the problems of existing sodium ion battery separator materials are solved, with low porosity, poor wetting, poor thermal stability and high cost, and the material's degradability and electrochemical performance are improved, which is in line with the concept of green environmental protection.
Patent Information
- Application Number
- CN202510336445.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The existing sodium ion battery separator materials have problems such as low porosity, poor wetting and poor thermal stability, and are high production costs and non-degradable, making them difficult to comply with the concept of green environmental protection.
Inexpensive iron, manganese metal compounds and organic ligands are used as raw materials to prepare coordinated polymer nanowire diaphragm materials through hydrothermal technology, and industrial waste and low-cost nitrogen-based triacetic acid are used as core raw materials to reduce production costs and reuse of waste raw materials.
The separator material has excellent electrochemical properties, wetting properties and high temperature resistance. It can quickly degrade in the natural environment, significantly reducing the environmental burden after battery waste and reducing production costs.
Smart Images

Figure CN119852642A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery materials, and in particular relates to a coordination polymer nanowire diaphragm material, a preparation method thereof, and an application thereof in the field of sodium ion batteries. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Lithium-ion batteries are widely used in consumer electronics, electric vehicles, and energy storage systems due to their high energy density and long cycle life. However, the scarcity and uneven distribution of lithium resources are likely to hinder the subsequent development of the lithium battery industry and the new energy industry. Sodium and lithium are in the same main group, have similar properties, and are abundant, evenly distributed, and inexpensive. Based on these advantages, sodium-ion batteries are considered an ideal choice for the next generation of large-scale energy storage technology.
[0004] As a key component of sodium-ion batteries, the diaphragm not only prevents the positive and negative electrodes from short-circuiting, but also provides a channel for the transmission of sodium ions. Its properties play a decisive role in battery performance and safety. At present, polyolefin diaphragms and glass fiber diaphragms are widely used in sodium-ion batteries. Among them, polyolefin diaphragms (such as polyethylene PE and polypropylene PP) have the problems of low porosity, poor wettability and poor thermal stability, and their raw materials rely on petroleum-based materials, and the production cost is high. Although the glass fiber diaphragm has good wettability and thermal stability, its thickness is large, which leads to increased internal resistance of the battery and decreased battery performance. In addition, the processing performance of the glass fiber diaphragm is poor, which limits its large-scale application in sodium-ion batteries. More importantly, these two types of diaphragms are difficult to degrade under natural environmental conditions, and they are easy to cause environmental pollution after being discarded, which is contrary to the concept of green environmental protection. The defects of commercial diaphragms in performance and process, especially the high cost and non-degradable problems, make it difficult for sodium-ion batteries to meet people's actual needs for energy storage batteries. Therefore, the development of a low-cost, green and degradable diaphragm material has become the focus of current research. Summary of the invention
[0005] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a diaphragm material suitable for sodium ion batteries, which overcomes the problems of low porosity, poor wettability and poor thermal stability of existing polyolefin diaphragms and glass fiber diaphragms, while reducing the production cost of diaphragm materials.
[0006] In order to achieve the above technical objectives, the present invention provides a method for preparing a coordination polymer nanowire diaphragm material, which uses cheap iron and manganese metal compounds and organic ligands as the raw material system, and in particular can use industrial waste (such as rust) and low-cost nitrilotriacetic acid as the core raw materials. The preparation is achieved through a simple hydrothermal process, without the need to configure complex equipment or add precious metal catalysts. First, the production cost is controlled and the reuse of waste industrial raw materials is achieved. In addition, the above diaphragm material also has excellent electrochemical properties, wetting properties and high temperature resistance, which perfectly overcomes the shortcomings of existing diaphragm materials.
[0007] Based on the above technical effects, the present invention provides the following technical solutions: In a first aspect, the present invention provides a method for preparing a coordination polymer nanowire membrane material, comprising the following steps: (1) dispersing a transition metal compound and nitrilotriacetic acid in a mixed solvent of an organic solvent and water, and subjecting the mixture to a hydrothermal reaction to obtain a reaction solution; (2) filtering the reaction solution to obtain a white solid, and drying overnight to obtain a solid powder; (3) The solid powder is dispersed in water after being dispersed, and the coordination polymer nanowire membrane material is obtained by papermaking and drying.
[0008] In the above step (1), the metal element in the transition metal compound can be selected from the elements of Group 3 to Group 12 of the periodic table, including scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), promethium (Pm), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho) , erbium (Er), thulium (Tm), ytterbium (Yb), lutetium (Lu) and other lanthanide elements, and the valence of the transition metal elements in the compound is mainly +2, +3; since the above preparation method has no strict restrictions on the types of metal elements in the transition metal compound, from the perspective of economic factors, those skilled in the art can conventionally select transition metal elements with lower cost and easier access, such as chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), etc.
[0009] Further, the compound form of the transition metal compound includes oxides, sulfides, halides, organic acid salts, inorganic acid salts, inorganic alkali salts or organic alkali salts of the above transition metal elements, and therefore, feasible examples of the transition metal compound include ferrous oxide, ferric oxide, ferric sulfide, ferric chloride, ferrous chloride, ferrous sulfate, ferrous sulfate, ferric nitrate, ferrous nitrate, ferric hydroxide, chromium trioxide, potassium chromate, chromium chloride, chromium sulfate, manganese monoxide, manganese dioxide, manganese trioxide, cobalt oxide, cobalt hydroxide, copper sulfate, copper hydroxide, copper nitrate, copper oxide, copper sulfide, cuprous chloride, cupric bromide, nickel monoxide, nickel oxide, nickel hydroxide, nickel sulfate, nickel chloride, nickel nitrate, etc. Those skilled in the art can make conventional selections from the above compounds based on factors such as the convenience and safety of raw material acquisition, and can even select industrial waste materials whose main components are the above compounds, such as rust, waste batteries, and mineral waste containing metals, etc., for cost considerations.
[0010] Furthermore, the organic solvent is preferably an alcohol or other organic reagent that is miscible with water in any proportion, and feasible examples include isopropanol, ethylene glycol, N,N-dimethylformamide, ethanol or methanol. In the mixed solvent, the volume ratio of water to the organic solvent is 1:3-10.
[0011] Furthermore, in the above step (1), the mass volume ratio of the transition metal compound, nitrilotriacetic acid and mixed solvent is 0.2 g: (0.1-2) g: (20-80) mL.
[0012] Furthermore, the temperature of the hydrothermal reaction is 80-180° C., more preferably 100-160° C.; the reaction time is 6-48 h, more preferably 12-48 h.
[0013] In the above step (2), the preferred drying temperature is 60-110°C and the drying time is 12-48 h; feasible drying methods include but are not limited to negative pressure drying, thermal radiation drying, etc.
[0014] In the above step (3), the preferred dispersion ratio of the solid powder to water is 0.4-2 g: 0.5 L. The deflaking and papermaking are common processes for pulping and making slurry into paper in the papermaking industry. Those skilled in the art can use a deflaking machine or a papermaking machine to achieve this. After papermaking is completed, it is dried at 60-110°C for 1-30 min to obtain a self-supporting film, and the diaphragm material is obtained by die stamping, and the preferred thickness is 25-125 μm.
[0015] The second aspect of the present invention provides a coordination polymer nanowire membrane material prepared by the method described in the first aspect.
[0016] The present invention investigates the heat resistance, degradation performance, wettability and electrochemical performance of the coordination polymer nanowire diaphragm material. It is verified that the diaphragm material can withstand relatively high temperatures, with an upper temperature limit of 250°C; it has good biodegradability, with a degradation rate of more than 90% within 15 days in a natural environment, significantly reducing the environmental burden after battery disposal; and the diaphragm material can also significantly improve the wetting effect of the electrolyte to ensure the free transmission of sodium ions during the charge and discharge process; when applied to sodium ion batteries, the diaphragm material has a higher voltage window (4.8 V), and the button battery used for assembly has excellent electrochemical performance.
[0017] The third aspect of the present invention provides the use of the coordination polymer nanowire membrane material described in the second aspect in a sodium ion battery.
[0018] A fourth aspect of the present invention provides a sodium ion button battery, which uses the coordination polymer nanowire diaphragm material described in the second aspect as a diaphragm.
[0019] The positive electrode of the sodium ion button battery is prepared as follows: Prussian blue, carbon black and polyvinylidene fluoride are mixed, N-methylpyrrolidone is added to prepare a uniform slurry, which is coated on an aluminum foil and dried to obtain the positive electrode.
[0020] The negative electrode of the sodium ion button battery is a sodium metal sheet.
[0021] The electrolyte of the sodium ion button battery is a ethylene carbonate / polycarbonate solution of NaClO4, wherein the concentration of NaClO4 is 0.8-1.2M, the volume ratio of ethylene carbonate / polycarbonate is 1:1, and the electrolyte also contains 4.5-5.5% of fluoroethylene carbonate (FEC) as an additive.
[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The coordination polymer nanowire diaphragm material provided by the present invention has the advantages of simple operation and wide source of raw materials. In particular, the iron-based compound raw materials can be obtained from industrial waste (such as rust, etc.). Combined with the low-energy hydrothermal process, the overall production cost is greatly reduced, providing significant economic advantages for large-scale applications.
[0023] 2. The coordination polymer nanowire diaphragm material provided by the present invention has a relatively small and ordered nanopore structure, and the surface of the nanowire is rich in functional groups. As a diaphragm material for sodium ion batteries, it can effectively improve the transmission efficiency of sodium ions and optimize the electrochemical performance of the battery.
[0024] 3. In addition, the above-mentioned diaphragm material also has good biodegradability, with a degradation rate of more than 90% within 15 days in the natural environment, which significantly reduces the environmental burden after the battery is discarded, and is in line with the development concept of green environmental protection. By adopting low-cost raw materials and simple processes, the present invention not only realizes the economical production of diaphragm materials, but also solves the environmental problem of non-degradable traditional diaphragms, and provides a new solution for the sustainable development of sodium ion batteries. It has important application significance in the field of battery diaphragm material technology, especially sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0026] Figure 1 This is a scanning electron microscope image of the coordination polymer nanowire membrane material prepared in Example 1; Figure 2 The heat resistance test results of the coordination polymer nanowire membrane material, commercial glass fiber membrane and commercial polyolefin membrane prepared in Example 1; Figure 3 The degradability test results of the coordination polymer nanowire membrane material prepared in Example 1, the commercial glass fiber membrane and the commercial polyolefin membrane; in, Figure 3 A is the initial morphology of the three membranes in a standard soil environment (0 day); Figure 3 B is the morphological comparison after 3 days of burial (same soil depth / humidity conditions); Figure 3 C is the morphological comparison after 15 days of burial (same soil depth / humidity conditions); Figure 4 The contact angle test result of the coordination polymer nanowire membrane material prepared in Example 1; in, Figure 4 A shows the test state before the droplet contacts the membrane surface at the initial state (0 seconds); Figure 4 B shows the wetting state of the droplet after it contacts the membrane surface for 0.05 seconds; Figure 5 The linear sweep voltammetry test results of a button cell assembled with the coordination polymer nanowire separator material prepared in Example 1 and a commercial glass fiber separator; Figure 6 The coordination polymer nanowire separator material prepared in Example 1 and a commercial glass fiber separator are assembled into a button cell and the performance results of charging and discharging at 1 C.
[0027] Figure 7 The performance results of a button-type full battery assembled with the coordination polymer nanowire separator material prepared in Example 1 and a hard carbon negative electrode at 1 C charge and discharge. DETAILED DESCRIPTION
[0028] It should be noted that the following detailed descriptions are all illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0029] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0030] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.
[0031] Example 1 In this embodiment, a coordination polymer nanowire membrane material is provided, and the preparation method of the material is as follows: (1) Weigh 0.2 g of ferric oxide and 0.5 g of nitrilotriacetic acid, add 40 mL of a 1:3 mixed solvent of water and isopropanol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 160°C and keep warm for 24 h to obtain a reaction solution; (2) filtering the reaction solution, and continuously injecting a water / ethanol mixture for washing during the filtering process to obtain a white solid, and drying the solid in a vacuum drying oven at 110° C. overnight to obtain a dry white powder; (3) Take 0.5 g of the obtained white powder and transfer it to 0.5 L of pure water, and disperse it completely by dispersing it. The dispersion is made into paper by a Kaiser sheet making machine. After drying at 100°C for 5 min, the self-supporting film is peeled off from the filter surface, and the coordination polymer nanowire diaphragm material can be obtained after mold stamping, which can be used as a sodium ion battery diaphragm.
[0032] Example 2 In this embodiment, another coordination polymer nanowire membrane material and a preparation method thereof are provided, which is different from that in Embodiment 1 in that step (1) is as follows: weigh 0.2 g of ferric oxide and 0.5 g of nitrilotriacetic acid, add 40 mL of a 1:10 mixed solvent of water / isopropanol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 160° C. and keep warm for 24 h to obtain a reaction solution.
[0033] Example 3 In this embodiment, another coordination polymer nanowire membrane material and a preparation method thereof are provided. The difference from Embodiment 1 is that step (1) is as follows: weigh 0.2 g of ferric oxide and 0.5 g of nitrilotriacetic acid, add 40 mL of a 1:3 mixed solvent of water / ethylene glycol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 100° C. and keep warm for 48 h to obtain a reaction solution.
[0034] Example 4 In this embodiment, another coordination polymer nanowire membrane material and a preparation method thereof are provided. The difference from Embodiment 1 is that step (1) is as follows: weigh 0.2 g of ferric oxide and 0.5 g of nitrilotriacetic acid, add 40 mL of a 1:3 mixed solvent of water / N,N-dimethylformamide, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 120° C. and keep warm for 48 h to obtain a reaction solution.
[0035] Example 5 In this embodiment, another coordination polymer nanowire membrane material and a preparation method thereof are provided. The difference from Embodiment 1 is that step (1) is as follows: weigh 0.2 g of ferric chloride and 0.5 g of nitrilotriacetic acid, add 40 mL of a 1:3 mixed solvent of water / isopropanol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 160° C. and keep warm for 12 h to obtain a reaction solution.
[0036] Example 6 In this embodiment, another coordination polymer nanowire membrane material and a preparation method thereof are provided. The difference from Embodiment 1 is that step (1) is as follows: weigh 0.2 g of ferrous sulfate and 0.2 g of nitrilotriacetic acid, add 40 mL of a 1:3 mixed solvent of water / isopropanol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 160° C. and keep warm for 12 h to obtain a reaction solution.
[0037] Example 7 In this embodiment, another coordination polymer nanowire membrane material and a preparation method thereof are provided. The difference from Embodiment 1 is that step (1) is as follows: weigh 0.2 g of ferrous chloride and 0.2 g of nitrilotriacetic acid, add 40 mL of a 1:3 mixed solvent of water / isopropanol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 160° C. and keep warm for 12 h to obtain a reaction solution.
[0038] Example 8 In this embodiment, another coordination polymer nanowire membrane material and a preparation method thereof are provided. The difference from Embodiment 1 is that step (1) is as follows: weigh 0.2 g of manganese chloride and 0.2 g of nitrilotriacetic acid, add 40 mL of a 1:3 mixed solvent of water / isopropanol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 160° C. and keep warm for 12 h to obtain a reaction solution.
[0039] Example 9 In this embodiment, another coordination polymer nanowire membrane material is provided, and the preparation method of the material is as follows: (1) Weigh 0.2 g of ferric oxide and 0.1 g of nitrilotriacetic acid, add 20 mL of a 1:3 mixed solvent of water and isopropanol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 160°C and keep warm for 24 h to obtain a reaction solution; (2) filtering the reaction solution, and continuously injecting a water / ethanol mixture for washing during the filtering process to obtain a white solid, and drying the solid in a vacuum drying oven at 60° C. for 48 hours to obtain a dry white powder; (3) Take 0.4 g of the obtained white powder and transfer it to 0.5 L of pure water. Disperse it completely by dispersing it. Make paper with the dispersion through a Kaiser sheet machine. After drying at 60°C for 30 min, peel off the self-supporting film from the filter surface and obtain a sodium ion battery separator after die stamping.
[0040] Example 10 In this embodiment, another coordination polymer nanowire membrane material is provided, and the preparation method of the material is as follows: (1) Weigh 0.2 g of ferric oxide and 2 g of nitrilotriacetic acid, add 80 mL of a 1:3 mixed solvent of water and isopropanol, stir magnetically until a homogeneous solution is formed, transfer to a polytetrafluoroethylene reactor, heat to 160°C and keep warm for 24 h to obtain a reaction solution; (2) filtering the reaction solution, and continuously injecting a water / ethanol mixture for washing during the filtering process to obtain a white solid, and drying the solid in a vacuum drying oven at 110° C. overnight to obtain a dry white powder; (3) Take 2 g of the obtained white powder and transfer it to 0.5 L of pure water. Disperse it completely by dispersing it. Make paper with the dispersion through a Kaiser sheet machine. After drying at 110°C for 1 min, peel off the self-supporting film from the filter surface and obtain a sodium ion battery separator after die stamping.
[0041] Comparative Example 1 The comparative example used was commercial Whatman glass fiber.
[0042] Performance Testing The diaphragms prepared in Examples 1-8 and Comparative Example 1 were cut into discs with a diameter of 19 mm and used as diaphragms for sodium ion batteries respectively. Prussian blue, carbon black and polyvinylidene fluoride were mixed in a mass ratio of 7:2:1, and N-methylpyrrolidone was added to grind in a mortar to make a uniform slurry, which was coated on aluminum foil and dried in a vacuum drying oven at 110°C. The pole pieces were cut into discs with a diameter of 12 mm as the positive electrode of the sodium ion battery, and the sodium sheet was used as the negative electrode of the sodium ion battery. The electrolyte was prepared by dissolving 1 M NaClO4 in a mixed solvent of ethylene carbonate (EC) and polycarbonate (PC) (volume ratio 1:1), and 5% fluoroethylene carbonate (FEC) was added as an additive. For the full battery, hard carbon was used as the negative electrode of the sodium ion battery. The battery was assembled in a glove box filled with argon, with a moisture content of less than 0.01 ppm and an oxygen content of less than 0.01 ppm. After assembly, the battery was subjected to a performance test of the charge and discharge specific capacity.
[0043] Figure 1 This is a scanning electron microscope image of the coordination polymer nanowire diaphragm material prepared in Example 1. It can be seen that the diaphragm material is a one-dimensional coordination polymer nanowire, which is composed of many thin and long nanowires stacked and crossed, and the surface of the nanowire has a small and ordered nanopore structure. The length of the nanowire can reach 50μm.
[0044] Figure 2 The results of heat resistance test. Heat resistance test conditions: polyolefin membrane (PP), coordination polymer nanowire membrane (Fe-NTA) prepared in Example 1, and commercial Whatman glass fiber (GF / D) in Comparative Example 1 were placed on an infrared microcrystal heating plate, and the temperature was gradually increased from room temperature to 200°C at intervals of 25°C. Each temperature point was kept constant for 1 hour, and the grid background recorded the deformation state. The experiment shows that Fe-NTA has no visible deformation before 150°C, which is better than the 125°C failure threshold of PP. At 200°C, both GF / D and Fe-NTA maintain complete morphology, but GF / D is an inorganic material (inherent heat resistance), while the organic coordination structure of Fe-NTA remains stable at this temperature.
[0045] Figure 3The following are the results of the degradation test. Degradability test conditions: Fe-NTA, PP and GF / D were buried in the soil of the flowerpot at the same depth, and the degradation of the above diaphragm materials was recorded at regular intervals. Figure 3 As shown, Fe-NTA can be degraded in the natural environment and is completely degraded after 15 days.
[0046] Figure 4 The contact angle test results are shown in Figure 2. Contact angle test conditions: using a contact angle meter, ethanol as the test liquid, and a high-speed camera system to record the droplet contact process. Figure 4 A (0 seconds) is the initial state before the droplet contacts, showing the critical contact point between the complete hemispherical droplet and the membrane surface; Figure 4 B (0.05 seconds) captures the wetting behavior of the droplet immediately after contact. The edge of the droplet spreads radially and the contact angle drops sharply to 28°, proving that Fe-NTA can induce ultrafast wetting of the droplet within a millisecond time scale.
[0047] Figure 5 The linear sweep voltammetry test results of button cells. The linear sweep voltammetry test conditions: sodium metal negative electrode / stainless steel positive electrode symmetrical battery structure, test voltage range 0-6 V, scan rate 0.001 V / s (Chenhua electrochemical workstation). The voltage window of GF / D is 4.6 V, while the voltage window of Fe-NTA reaches 4.8 V, indicating that the latter has a wider operating voltage range.
[0048] Figure 6 The charge and discharge specific capacities of sodium ion batteries assembled with Fe-NTA and GF / D respectively at a current density of 1 C. The results show that after 500 cycles, the capacity retention rate of the sodium ion battery assembled with Fe-NTA is 75.6%, while the capacity retention rate of the sodium ion battery assembled with GF / D is 60.9%, indicating that the coordination polymer nanowire diaphragm material provided by the present invention can be used as a diaphragm material to effectively improve the service life of sodium ion batteries.
[0049] Figure 7 The performance results of the button-type full cell assembled with Fe-NTA and hard carbon anode (PBA||HC) at 1 C charge and discharge: the first cycle discharge capacity of the battery is 67.1 mAh g −1 After 100 cycles, it still maintains 60.7 mAh g −1 , the capacity retention rate reached 90.5%. This proves that the coordination polymer nanowire diaphragm material provided by the present invention can optimize the electrochemical performance as a diaphragm material in a complete battery system.
[0050] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a coordination polymer nanowire membrane material, characterized in that: The steps include: (1) dispersing a transition metal compound and nitrilotriacetic acid in a mixed solvent of an organic solvent and water, wherein the mass volume ratio of the transition metal compound, nitrilotriacetic acid, and the mixed solvent is 0.2 g: 0.1-2 g: 20-80 mL; and subjecting the mixture to a hydrothermal reaction to obtain a reaction solution; The transition metal compound is selected from one of ferric oxide, ferric chloride, ferrous sulfate, ferrous chloride, and manganese chloride. The temperature of the hydrothermal reaction is 100-160° C. and the reaction time is 12-48 hours. (2) filtering the reaction solution to obtain a white solid, and drying overnight to obtain a solid powder; (3) The solid powder is dispersed in water after being dispersed, and the coordination polymer nanowire membrane material is obtained by papermaking and drying.
2. The method for preparing the coordination polymer nanowire membrane material according to claim 1, characterized in that: In step (1), the organic solvent is selected from isopropanol, ethylene glycol, N,N-dimethylformamide, ethanol or methanol; in the mixed solvent, the volume ratio of water to the organic solvent is 1:3-10.
3. The method for preparing the coordination polymer nanowire membrane material according to claim 1, characterized in that: In step (2), the drying temperature is 60-110° C. and the drying time is 12-48 h.
4. The method for preparing the coordination polymer nanowire membrane material according to claim 1, characterized in that: In step (3), the dispersion ratio of the solid powder to water is 0.4-2 g:0.5 L.
5. The method for preparing the coordination polymer nanowire membrane material according to claim 1, characterized in that: In step (3), after papermaking is completed, the paper is dried at 60-110° C. for 1-30 min to obtain a self-supporting film, which is then punched through a mold to obtain the diaphragm material with a thickness of 25-125 μm.
6. The coordination polymer nanowire membrane material prepared by the method according to any one of claims 1 to 5.
7. Use of the coordination polymer nanowire diaphragm material according to claim 6 in sodium ion batteries.
8. A sodium ion button battery, characterized in that: The coordination polymer nanowire diaphragm material according to claim 6 is used as a diaphragm.
9. The sodium ion button battery according to claim 8, characterized in that: The positive electrode of the sodium ion button battery is prepared as follows: Prussian blue, carbon black and polyvinylidene fluoride are mixed, N-methylpyrrolidone is added to prepare a uniform slurry, which is coated on an aluminum foil and dried to obtain the positive electrode.
10. The sodium ion button battery according to claim 8, characterized in that: The negative electrode of the sodium ion button battery is a sodium metal sheet; The electrolyte of the sodium ion button battery is a NaClO4 ethylene carbonate / polycarbonate solution, wherein the concentration of NaClO4 is 0.8-1.2M, the volume ratio of ethylene carbonate / polycarbonate is 1:1, and the electrolyte also contains 4.5-5.5% fluoroethylene carbonate as an additive.
Citation Information
Patent Citations
Biomass fiber-based battery diaphragm as well as preparation method and application thereof
CN116706428A
Composite diaphragm coated with metal organic framework mixture and preparation method of composite diaphragm
CN117154343A
Preparation method and application of coordination compound derived ferro-nickel bimetallic sulfide nitrogen-doped carbon composite nanowire
CN118598222A
Composite material, separator, battery and electric device
CN119340609A
Coated separator with anion receptor and lithiumsecondary battery including the same
KR1020070080149A